Latar Belakang Munculnya Ikhtilaf pada Persoalan Furu’ - Yusra Dewi Siregar (Jurnal Akademika Kajian Ilmu-Ilmu Sosial, Humaniora Dan Agama, 2022)
Buwaihi dynasty is one of the greatest dynasties on the Moslem era. Buwaihi is the name of a family that came from Persia. They were strong so they became armies of the Moslem soldiers. They could spread Moslem territory in the world. But it was not for a long time. At the end their authority became ruined